Chitin Facilitated Mineralization in the Eastern Oyster - Chan, Vera Bin San; Johnstone, Mary Beth; Wheeler, A. P.; Mount, Andrew S. (Frontiers in Marine Science, 2018)
Chitin is often reported in molluscan shell, where it likely contributes to the mechanical strength of the biomineral. However, the role of this polysaccharide in relation to the process of shell formation is not well understood. We investigated the deposition of chitin during shell repair in the Eastern oysters, Crassostrea virginica, by inserting stainless steel and glass implants in a region of shell damage. This work documents the time course of deposition of both chitin fibrils and calcium carbonate layers. Chitin is detected by confocal laser scanning microscopy (CLSM) using a chitin-specific fluorescent probe that was produced from clones of a chitin-binding domain. The presence of fibrils was confirmed using electron microscopy of implants. The fibrils’ dimensions were reduced after treatment with both acid and bleach, suggesting that chitin interacts with inorganic minerals and other organic components such as proteins and lipid as early as in 5 hours after shell damage. With CLSM, it was shown that chitin co-localized with membrane, suggesting the importance of cells located on the implants in the process of fibril formation. Using observations from this study as well as those from the literature on chitin synthase production in molluscs and fungi, we propose a cellular mechanism of chitin deposition related to shell formation.